KEBIASAAN MAKAN SAYUR DAN BUAH IBU SAAT KEHAMILAN KAITANNYA DENGAN KONSUMSI SAYUR DAN BUAH ANAK USIA PRASEKOLAH - Febriana, Rizka; Sulaeman, Ahmad (Jurnal Gizi dan Pangan, 2014)
The aim of this study was to analyze the preferences and consumption levels on fruit and vegetables among pre school-aged children and its relation with the habit of their mother in consuming vegetable and fruit during pregnancy. Cross sectional design with purposive sampling on 102 early childhood school students in Tanah Baru Village, Beji, Depok was applied in this study. Almost all 99.0% subject consumed less vegetable (<150 g/day) and 74.5% consumed less fruit (<100 g/day). About 57.7% subject liked vegetable and 77.5% liked fruit. Variables related to subject vegetable and fruit consumption were mother’s support, per capita income, subject preference, and morbidity score on vegetable (p<0.05). Meanwhile, variables related to subject preference on vegetable and fruit were mother’s preference during pregnancy, vegetable and fruit consumption frequency of mother during pregnancy, and the age of initial introduction on fruit (p<0.05). Factors affected subject preference on vegetable and fruit was mother’s preference during pregnancy, moreover mother’s support also affected subject preference towards vegetable.